The Systematic Demonization of the Palestinian Resistance and its Impact on the Libertarian Course of The Palestinian Cause - Boudjemaa HAMMAD; Mohammed BEACEL (UNIVERSITÉ MOHAMED BOUDIAF - M’SILA, 2024)
This study addresses the problem of demonizing the Palestinian resistance, so whether by powerful Western countries or by some Arab countries. The focus has been on the role of the media in the demonization process. The political, economic and social effects of this demonization on the issue of liberating Palestine from the Israeli occupation were also discussed. This topic was divided into two main chapters. In the first chapter, we discussed the theoretical and historical framework of the Palestinian issue and resistance. The second chapter also dealt with the demonization of the Palestinian resistance at the international, regional and media levels and its effects on the liberation of the State of Palestine and the independence of the Palestinian people from the Israeli occupation in recent years, especially after October 7, 2023. The main research problem was the attempt to find out the ways in which the Palestinian resistance is systematically demonized in the media, international discourse, and political discourse. So it was used the descriptive method, in a critical analytical manner. The media influence approach and conflict theory was also used. This study reached a set of results, including The Zionist movement seeks to demonize the PR by all media and political means, and at the regional and international levels. It was also concluded that the Palestinian resistance, with all its factions, is rooted in Palestinian society. In addition to what was mentioned above, the recent Israeli aggression on Gaza since October 7, 2023 revealed the Zionist movement is using Western and Arab media in support of the Israeli occupation and is spreading rumors about the demands of the Palestinian people to gain their legitimate and just independence. The systematic demonization of the PR has a profound and detrimental impact on the libertarian trajectory of the Palestinian cause. It distorts public perception, influences international policies, marginalizes Palestinian voices, and detracts from the core principles of freedom and justice.
Keywords: The Palestinian issue. Palestinian resistance. Demonization. The media